ANALYSIS OF THE EFFECTIVENESS OF DUAL PI3K/mTOR INHIBITORS IN INHIBITION OF PI3K/AKT/mTOR SIGNALING PATHWAY IN BREAST CANCER - Susanto, Andi; Subardin, Dian Aryanti; Gunadi, Julia Windi; Sanjaya, Ardo (Medika Kartika : Jurnal Kedokteran dan Kesehatan, 2025)
Breast cancer is a malignancy originating from breast cells, ducts, and tissues that can occur due to genetic mutations due to DNA damage in normal cells. The PI3K/Akt/mTOR pathway is an intracellular pathway that plays an important role in regulating basic cell functions such as cell growth, movement, survival, metabolism, and angiogenesis. Some examples of PI3K/mTOR pathway inhibitor drugs on the market and often used are dactolisib, samotolisib, voxtalisib, and so on. These drugs are more effective than single-pathway inhibitors. This article was prepared using the literature review method. The data used in this article were obtained from the PubMed and Google Scholar using the keywords breast cancer, PI3K/Akt/mTOR inhibitor, and PI3K/AKT/mTOR signaling pathway. Several studies suggest that the PI3K-AKT-mTOR pathway is critical in mediating the proliferation and migration of breast cancer cells. Because of the importance of the PI3K-AKT-mTOR pathway in the pathogenesis of breast cancer, it is often used as a target for breast cancer therapy. PI3K/mTOR dual ATP competitive inhibitors can directly act on the main target proteins of PI3K and mTOR, thereby more efficiently inhibiting the PI3K/AKT/mTOR signaling pathway and effectively preventing other factors that can activate the PI3K pathway, and reducing the resistance and side effects produced by single inhibitors. Keywords: breast cancer, dual inhibitor, PI3K-AKT-mTOR DOI : 10.35990/mk.v8n4.p434-445